Revisit Intention for Medical Services: An Investigation on Penang as a Medical Tourism Hub - Yong, Siew-Pin; Goh, Yen-Nee; Ting, Mao-Seng; Janifer, Lunyai (Elsevier, 2021)
This research investigates medical tourists' revisit intention formation by utilizing critical concepts of medical quality, service quality, effective communication, satisfaction, and price reasonableness. A survey was conducted via face-to-face questionnaires to medical tourists who had received medical treatment or healthcare services at Penang hospitals. Perceived medical and service quality has significant associations affecting intentions to revisit hospitals, and satisfaction acted as a significant mediator between medical quality and satisfaction. However, the moderating role of price reasonableness is not supported. The implication of the Push and Pull Motivation Theory and practice are further discussed in this study.